United States. Continental Army. 6th Maryland Regiment orderly book - United States. Continental Army. Maryland Regiment, 6th.
Orderly book (169 pages; 1780 April 4-August 10) containing daily reports from campaigns in New Jersey, Virginia, and elsewhere.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Army -- Order-books.; New Jersey -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Campaigns; Virginia -- History -- Revolution, 1775-1783.